1992
DOI: 10.1007/bf01957566
|View full text |Cite
|
Sign up to set email alerts
|

The role of sonography in the evaluation of gastro-oesophageal reflux-correlation to pH-metry

Abstract: Sonography was compared to pH-metry and/or oesophagomanometry to evaluate the accuracy of sonography in the early diagnosis of gastro-oesophageal reflux. Thirty children with a mean age of 72 days (21-252 days) were studied. The results showed that specificity of sonographic diagnosis was 87.5% and sensitivity was 100% (with P less than 0.001). Sonography also proved helpful in providing both functional and morphological data in addition to pH-metric results. This study therefore suggests that sonography is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
0
26
1
2
Order By: Relevance
“…hiatus hernia, malrotation) [8] along with the valuable experiences that practitioners have acquired through the years since the 1980s, ultrasonography (US) has been used as an alternative to BS in the diagnosis of GERD [9]. Esophageal US has been described as a noninvasive, readily available, repeatable, cheap, and fast technique that could be commonly used in the diagnosis and follow-up of young children with GERD [10][11][12][13][14][15]. Comparative studies of transabdominal US and BS demonstrated that US presents a higher sensitivity in the diagnosis of GERD [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…hiatus hernia, malrotation) [8] along with the valuable experiences that practitioners have acquired through the years since the 1980s, ultrasonography (US) has been used as an alternative to BS in the diagnosis of GERD [9]. Esophageal US has been described as a noninvasive, readily available, repeatable, cheap, and fast technique that could be commonly used in the diagnosis and follow-up of young children with GERD [10][11][12][13][14][15]. Comparative studies of transabdominal US and BS demonstrated that US presents a higher sensitivity in the diagnosis of GERD [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal ultrasonography (US) is a non-invasive, readily available, repeatable, cheap, fast and highly sensitive technique [1][2][3][4] in the diagnosis of gastroesophageal reflux (GER) in infants and children [5][6][7][8] . The esophageal US studies in GER have mainly focused on the evaluation o f t h e g a s t r o e s o p h a g e a l j u n c t i o n ( G E J ) [ 9 -1 1 ] a n d esophageal motility [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Gastro-oesophageal reflux (GOR) is a common condition in early infancy [1,2] characterised by the retrograde flow of gastric contents into the oesophagus [2] . Because of potentially serious sequelae, early diagnosis and treatment in these patients is extremely important.…”
Section: Introductionmentioning
confidence: 99%